2016
DOI: 10.1016/j.watres.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Removal of phages and viral pathogens in a full-scale MBR: Implications for wastewater reuse and potable water

Abstract: Please cite this article as: Purnell, S., Ebdon, J., Buck, A., Tupper, M., Taylor, H., Removal of phages and viral pathogens in a full-scale MBR: Implications for wastewater reuse and potable water, Water Research (2016),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 30 publications
7
43
0
1
Order By: Relevance
“…The effect of frequency on removal efficiency operated at 20 mL/minute and operating time at 120 minute is displayed in Figure 3a The highest RE with respect to FC was similar to those obtained in previous studies [7,9,18,19]. However, the RE with respect to FC in the present study was higher than that achieved using floating media filter-microfiltration without and with coagulant [18], combination of MBR and chlorination [19], adsorption using a graphite adsorbent with electrochemical regeneration [8,12], and a membrane bioreactor [15]. The REs with respect to FC and TC were quite similar to those using pulsed high voltage [7] and were higher than those using RFICP in a batch experiment and …”
Section: -3supporting
confidence: 85%
“…The effect of frequency on removal efficiency operated at 20 mL/minute and operating time at 120 minute is displayed in Figure 3a The highest RE with respect to FC was similar to those obtained in previous studies [7,9,18,19]. However, the RE with respect to FC in the present study was higher than that achieved using floating media filter-microfiltration without and with coagulant [18], combination of MBR and chlorination [19], adsorption using a graphite adsorbent with electrochemical regeneration [8,12], and a membrane bioreactor [15]. The REs with respect to FC and TC were quite similar to those using pulsed high voltage [7] and were higher than those using RFICP in a batch experiment and …”
Section: -3supporting
confidence: 85%
“…However, given the potential risks associated with disinfection byproducts, there has been recent interest in evaluating whether MBR effluents can be directly reused for irrigation and other applications (Purnell et al 2016). As a result, the risks arising from pathogenic bacteria detected by dPCR to workers potentially irrigating with the full-scale AeMBR effluent were evaluated using QMRA.…”
Section: Discussionmentioning
confidence: 99%
“…Purnell, et al [5] monitored the behavior of phages and viral pathogens in a full-scale membrane bioreactor (MBR) based water-recycling system. Their results indicated that the combination of chlorination and MBR technology appears to have significant potential in removing bacteria (fecal coliforms and enterococci) but is not effective in removing viral pathogens (adenovirus).…”
Section: Profile Of Disinfection Efficiency Of Salmonella Typhimentioning
confidence: 99%
“…Alternative technologies in drinking water treatment processes have been investigated using physical methods such as a membrane bioreactor [5], pulsed electric field irradiation [6], and floating media filtermicrofiltration [7]. The advanced oxidation process (AOP) is an alternative process for removing pathogenic bacteria from water.…”
Section: Introductionmentioning
confidence: 99%